Investigation of the acoustic behavior of oil palm (Elaeis guineensis) frond fiber at various weights - Tajuddin, Tajuddin; Husaini, Husaini; Suhaeri, Suhaeri (Politeknik Negeri Lhokseumawe, 2025)
The increasing demand for sustainable materials in noise control applications has driven interest in natural fiber-based sound absorbers. This study investigates the potential of oil palm frond fiber (Elaeis guineensis) as an alternative to synthetic acoustic materials. The fibers were extracted, dried, and hot-pressed at 200°C into 100 mm × 10 mm cylindrical samples with varying weigh of 20–60 g. Pore morphology and composition were analyzed using SEM–EDX, while sound absorption coefficients (α) were measured using an impedance tube (ISO 10534-2) across 125–4000 Hz. SEM–EDX results revealed a highly porous structure dominated by carbon (57.5%) and oxygen (41%), confirming the organic nature of the fibers. The material exhibited strong absorption in the mid- to high-frequency range (500–4000 Hz), with α = 0.99 at 4000 Hz and a maximum NRC of 0.89 at 50 g. Optimal performance occurred at 40–50 g, with α 0.95 between 500 and 2000 Hz, while low-frequency absorption (250 Hz) remained limited (α = 0.1–0.6). Overall, oil palm frond fiber demonstrates significant potential as a low-cost, biodegradable, and sustainable acoustic material for medium- to high-frequency applications, such as interior acoustic panels and building insulation systems.